Service mantra of the Grameen banks of India in the post-merger era - Sulagna Das (Rajagiri Management Journal (RAMJ), 2022)
Purpose: This paper aims to find out the performance of the Grameen Banks of West Bengal after their merger. Design/methodology/approach: The objective of the paper is to measure the performance of Paschim Banga Gramin Bank (PBGB) and Bangiya Gramin Vikash Bank (BGVB) after their amalgamation, to compare the performance of PBGB and BGVB, using the key performance indicators and to analyze the future scope of these two banks. The factors that are considered for this study are number of branches (if these banks could reach maximum of the rural mass), number of staffs (if these banks generated employment after the merger), investments, deposits, composition of total funds (owned funds and borrowed funds), lending services, productivity per branch and per staff, etc. The study uses statistical tools to analyze the data. Findings: It has been observed that there exists a significant difference in the "Branch Network" of PBGB and BGVB. A significant difference has been observed in the "Number of Staffs" of PBGB and BGVB. It has been found that there is a significant difference in the "three type of funds" of PBGB and BGVB. It has been found that there is a significant difference in the "Investments" of PBGB and BGVB. A significant difference has been observed in the "Deposits" of PBGB and BGVB. It has been found that there is a significant difference in the "Outstanding Loan" amount of PBGB and BGVB. It has been observed that there is a significant difference in the "Loan Issued" amount of PBGB and BGVB. It has been found that there is no significant difference in the Productivity "Per Branch" and "Per Employee" of PBGB and BGVB. Research limitations/implications: The study is based on the published/secondary data and is restricted to two Regional Rural Banks of West Bengal, the PBGB and the BGVB, for nine years, 2012-2020. Social implications: The paper will help the future researchers, to know the performance of the Grameen Banks for the study period; this will help them to carry on with the study in the future. Originality/value: The work is original and never sent to anywhere else for publication.
Keywords: 650; Microfinance; Service; Key performance indicators; Grameen banks; Post-Merger; Bangiya Gramin Vikash Bank (BGVB); Paschim Banga Gramin Bank (PBGB)